ISSN 2615-5788 Print (2615-7764) Vol 12 No. 2 @ 2025 Wildan Surya Wijaya, Muhammad Risfan Ramadhani. Jurnal Teknik Elektro dan Komputer TRIAC 2025 Yunia Dwie Nurcahyanie, Muhamad Abdul Jumali https://journal.trunojoyo.ac.id/triac - Wildan Surya Wijaya; Muhammad Risfan Ramadhani; Yunia Dwie Nurcahyanie; Muhamad Abdul Jumali (Jurnal Teknik Elektro dan Komputer TRIAC, 2025)
The use of small-scale solar energy is one of the strategic solutions for electricity needs in remote areas and outdoor activities. As the need for portable electrification increases, the development of solar backpack systems is becoming a practical and sustainable alternative. This research aims to design and test a portable backpack system based on a thin film solar panel with a capacity of 20 Wp, equipped with a 12V solar charge controller and a 7.2 Ah battery. The system is designed with two outputs, namely 12V DC and 5V USB, to support lightweight devices such as LED lights and smartphones. The test was carried out at two different locations, namely Mount Lorokan and Mount Penanggungan, with data taken which included latitude, longitude, solar elevation angle, PV voltage, PV current, and output power. The measurement results show that there is a variation in the performance of solar panels according to geographical conditions and solar elevation angles. On Mount Lorokan, the peak power reaches 8.55 W at an angle of 75°, while on Mount Penanggungan the maximum power is slightly higher, which is 8.6 W at an angle of 78°. Mount Lorokan excels at maximum power, Penanggungan shows more stable performance at low to medium angles. This research contributes to the development of a portable electrification system based on renewable energy that supports power continuity in locations without access to electricity.